Air Pollution Monitoring System Using IoT - Mohd Sofri, Muhammad Hafizuddin; Adan, Nor Faezah; Jefree, Nurul Humairah; Sulaiman, Muhammad Danial Hafiz (Multidisciplinary Applied Research and Innovation, 2022)
Air pollution levels are rising year after year in Malaysia. It is because Malaysia is a developing country, this is the case. Many developments result in numerous contaminants, particularly air pollution. For instance, there was a big case in Pasir Gudang, Johor, where pollution caused shortness of breath and vomiting [1], as well as the Covid-19 crisis, which was partly caused by poor air quality. Besides, fine particles are most harmful air pollutants to humans. They are easily transported from outdoor to indoor air [2].  As a result, we require systems that can detect and quantify air pollution. The major goal of using to create an Air Pollution Level Monitoring System using IoT is to identify air pollution levels in places with severe, moderate, and good air quality in order to combat the growing problem of air pollution. It must be accomplished in order to live a better and healthier life in the future. We propose a system that uses the Internet of Things to monitor and check air quality. This project is produced using  Arduino software to collect data for the air pollution level monitoring system, which is then transferred directly to the blynk application. The information gathered will be presented in the form of air quality and air danger ratings [3].